The relationship between executive compensation structure and CSR in Chinese listed firms - Zhu, Sha (2020)
The purpose of this paper is to investigate the role of executive compensation structure, split between short-term (cash-based) compensation and long-term (equity-based) compensation, in relation to corporate social responsibility performance in the Chinese listed firms and how the association varies within state-owned enterprises (SOEs) and non-state-owned enterprises (Non-SOEs). Based on a sample of 302 Chinese lister firms over the period 2015-2017. The results show that both short-term compensation and long-term compensation have an impact on CSR. Specifically, short-term executive compensation has a positive association with CSR performance, and long-term compensation has a negative relationship with CSR performance. Furthermore, the cash-based compensation executed in SOEs is more attractive for executives to be encouraged to implement CSR than that in Non-SOEs. The paper has important implications for designing the executive incentive plan and confirms the prominent role of the executive about CSR decisions in China. Previous studies on the relationship between executives’ compensation and CSR has mainly focused on developed countries, like the U.S. and Canada. This study is set in an emerging economy and identifies new evidence to show that executive incentives' effect is institutionally specific.